PREVALENCE OF LOW BACK PAIN AND AWARENESS OF PHYSIOTHERAPY INTERVENTIONS AMONG WELDERS IN NNEWI, ANAMBRA STATE, NIGERIA: A CROSS-SECTIONAL STUDY (Journal of Biomedical Investigation, 2025)
Background: Low back pain (LBP) is a major occupational health problem among workers in physically demanding jobs. Welders are particularly susceptible due to prolonged bending, awkward postures, and heavy lifting. Despite the established effectiveness of physiotherapy in managing musculoskeletal disorders, awareness and utilization of physiotherapy services remain critically low among informal sector workers in Nigeria.Aim: This study investigated the prevalence of LBP and assessed whether welders in Nnewi North Local Government Area (L.G.A.), Anambra State, were aware of physiotherapy interventions.Materials and Methods: A descriptive cross-sectional survey was conducted among 67 male welders (mean age 34.25 ± 7.79 years) selected via purposive sampling. Data were collected using the Modified Nordic Musculoskeletal Questionnaire (NMQ; Cronbach's α = 0.79) and a structured Awareness of Physiotherapy Questionnaire (adapted from Maruf et al., 2012; Cronbach's α = 0.81). Descriptive statistics (frequencies, percentages) and inferential statistics (Chi-square and Fisher's Exact tests) were used for analysis (α ≤ 0.05).Results: The 12-month prevalence of LBP was 53.7%, with 40.3% reporting activity limitation due to pain. Only 13.4% of respondents were aware of physiotherapy, with family/friends as the exclusive source of information (100%). Among the nine respondents who were aware, none demonstrated any knowledge of what physiotherapy involves or the conditions it manages. A statistically significant association was found between experiencing LBP and awareness of physiotherapy (χ² = 7.10, p = 0.008).Conclusion: LBP is highly prevalent among welders in Nnewi North L.G.A., yet awareness of physiotherapy interventions is critically low. Awareness is predominantly reactive, arising from personal pain experience rather than structured occupational health education. Targeted outreach and integration of physiotherapy into primary and occupational healthcare services are urgently needed.
Keywords: Low Back Pain; Metal Workers; Cross-Sectional Studies; Occupational Health; Prevalence; Nigeria; Health Education; Surveys and Questionnaires; Posture; Informal Sector